2017
DOI: 10.1556/018.68.2017.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The chemical inducer, BTH (benzothiadiazole) and root colonization by mycorrhizal fungi (Glomus spp.) trigger resistance against white rot (Sclerotinia sclerotiorum) in sunflower

Abstract: White rot caused by Sclerotinia sclerotiorum (SS) is one of the most devastating plant diseases of sunflower. Controlling this pathogen by available tools hardly result in acceptable control. The aim of this study was to elucidate the effects of plant resistance inducers, BTH (benzothiadiazole in Bion 50 WG) and arbuscular mycorrhizal fungi (AMF) on disease development of white rot in three sunflower genotypes. Defence responses were characterized by measuring the disease severity and identifying cellular/ his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…Iriti and Faoro, (2003) showed that in bean cultivars against rust (Uromyces appendiculatus) Bion induce resistance and controlled the bean rust over all the tested cultivars. The same was obtained by Guo and Stotz, 2007;Azami-Sardooei et al (2013) and Bán et al (2017) who indicated that foliar applications of Bion reduced B. cinerea on cucumber and sunflower and white mold (S. sclerotiorum) disease on bean besides both systemic and localized inductions of resistance were observed. Gaffney et al (1993); Sticher et al (1997) and Kumar, (2014) reported that Salicylic acid (SA) plays an important role in the induction of plant defense as plant hormone against plant diseases via various host-pathogen interactions.…”
Section: Discussionsupporting
confidence: 73%
“…Iriti and Faoro, (2003) showed that in bean cultivars against rust (Uromyces appendiculatus) Bion induce resistance and controlled the bean rust over all the tested cultivars. The same was obtained by Guo and Stotz, 2007;Azami-Sardooei et al (2013) and Bán et al (2017) who indicated that foliar applications of Bion reduced B. cinerea on cucumber and sunflower and white mold (S. sclerotiorum) disease on bean besides both systemic and localized inductions of resistance were observed. Gaffney et al (1993); Sticher et al (1997) and Kumar, (2014) reported that Salicylic acid (SA) plays an important role in the induction of plant defense as plant hormone against plant diseases via various host-pathogen interactions.…”
Section: Discussionsupporting
confidence: 73%
“…Azami-Sardooei et al (2013) investigated the effects of foliar applications of different concentrations of BTH on resistance to B. cinerea on bean and cucumber, only concentrations of 250 mg/l and higher, strongly reduced susceptibility against B. cinerea. Recently, Bán et al (2017) found that the application of Bion reduced sunflower white mold (S. sclerotiorum) disease symptoms; besides both localized and systemic inductions of resistance were observed. Salicylic acid (SA) is a phenolic plant hormone which plays an important role in regulating defenses in plants against biotrophic and hemibiotrophic pathogens, however signaling pathways mediated by salicylic acid (SA) are widely studied in various hostpathogen interactions (Gaffney et al, 1993 andSticher et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…AMF compete with pathogenic fungi for colonization sites, space, and photosynthesis. Similarly, Bán et al [ 120 ] showed that the inoculation with AMF belonging to the Glomus genus led to localized and systemic resilience to white rot ( Sclerotinia sclerotiorum ) in sunflower.…”
Section: Building Resilience: Harnessing Mycorrhizal Symbiosis For En...mentioning
confidence: 99%